Content and Form Anaysis of the Web Sites of University Libraries: A study on the Case in Turkey - Mesut Kurulgan; Fatih Bayram (Türk Kütüphaneciliği)
Internet is an important medium in the process of development of information and information technologies. University library web sites are used by many users to reach information. The speed, ease and efficiency of library web site usage contributes to users' satisfaction. This study compares library web sites of state universities to the foundation universities in terms ofform and content. Evaluation criteria obtained through content analysis is measured by visiting each library Web site and measures are given as frequency distribution and percentage analysis. The study concludes that library web sites of state universities use the Internet opportunities more effectively than the library web sites of foundation universities.